2018
DOI: 10.1161/circinterventions.118.006699
|View full text |Cite
|
Sign up to set email alerts
|

Response by Schneider et al to Letter Regarding Article, “Treatment Effect of Drug-Coated Balloons Is Durable to 3 Years in the Femoropopliteal Arteries: Long-Term Results of the IN.PACT SFA Randomized Trial”

Abstract: E ndovascular intervention has become the primary mode of revascularization for patients with symptomatic femoropopliteal peripheral artery disease. Multiple modalities of treatment exist; however, the mainstay is percutaneous transluminal angioplasty (PTA) and implantation of a bare metal stent (BMS). 1 Angioplasty, though effective in luminal gain, has been associated with restenosis rate of up to 60% at 12 months. 2,3 Although implantation of a BMS has been shown to reduce this restenosis rate by nearly hal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
83
0
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 61 publications
(89 citation statements)
references
References 18 publications
4
83
0
2
Order By: Relevance
“…The nonsignificant RR of mortality was 1.33 with a CI that crossed null ( P = 0.08) and the trend became less apparent with omission of data from the THUNDER study which carried the greatest relative strength. Our findings are consistent with findings from the IN PACT SFA trial which found no association between paclitaxel‐coated balloon use and mortality. Interestingly a recent meta‐analysis published by Katsanos et al compared paclitaxel devices (both stents and balloons) in FPD to nondrug‐coated treatment device and reported higher mortality both at 2‐year and 5‐year follow‐up.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The nonsignificant RR of mortality was 1.33 with a CI that crossed null ( P = 0.08) and the trend became less apparent with omission of data from the THUNDER study which carried the greatest relative strength. Our findings are consistent with findings from the IN PACT SFA trial which found no association between paclitaxel‐coated balloon use and mortality. Interestingly a recent meta‐analysis published by Katsanos et al compared paclitaxel devices (both stents and balloons) in FPD to nondrug‐coated treatment device and reported higher mortality both at 2‐year and 5‐year follow‐up.…”
Section: Discussionsupporting
confidence: 91%
“…Primary patency rates (freedom from TLR) at 1 follow‐up were significantly higher in patients with Lutonix DCB when compared to POBA (65.2% vs. 52.6%, P = 0.02). IN PACT Admiral SFA (Medtronic, Minneapolis, MN) prospective single blind RCT trial compared paclitaxel‐coated DCB versus POBA for treatment of FPD . Primary patency rates (82.2% vs. 52.4%; P < 0.001) were higher and clinically driven TLR (2.4% vs. 20.6%; P < 0.001) was significantly lower in patients with DCB when compared to POBA at 12 months.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, whether stents should be first‐line treatment for PVD is questionable. The recently published IN.PACT SFA trial showed for the treatment of femoropopliteal disease, the paclitaxel‐coated DEB had significantly higher patency and a lower rate of repeat interventions compared to balloon angioplasty. The average lesion treated in the DEB group was 89.4 mm; at 3 years, the target vessel patency was 69.5%, and freedom from clinically driven TLR was 84.5% in the DEB group.…”
mentioning
confidence: 99%